Employee Selection as a Control System - CAMPBELL, DENNIS (Journal of Accounting Research, 2012)
ABSTRACT Theories from the economics, management control, and organizational behavior literatures predict that when it is difficult to align incentives by contracting on output, aligning preferences via employee selection may provide a useful alternative. This study investigates this idea empirically using personnel and lending data from a financial services organization that implemented a highly decentralized business model. I exploit variation in this organization in whether or not employees are selected via channels that are likely to sort on the alignment of their preferences with organizational objectives. I find that employees selected through such channels are more likely to use decision‐making authority in the granting and structuring of consumer loans than those who are not. Conditional on using decision‐making authority, their decisions are also less risky ex post. These findings demonstrate employee selection as an important, but understudied, element of organizational control systems.